THE APPLICATION OF JIGSAW TYPE OF COOPERATIVE LEARNING MODEL IN MATHEMATICS SUBJECT TO INCREASE STUDENTS' LEARNING OUTCOMES - Maman Rahman; Dahlan Dahlan (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Abstract The background of this research is from the results of initial observations which show that the children only listen, take notes, memorize, and students are not active to be able to find their own concepts, so it resulting in low learning outcomes. With that background, the researchers took the initiative to make improvements using the Jigsaw-Type Cooperative method. The result of this classroom action research, obtain that: 1) Students' learning outcomes in mathematics subjects before using jigsaw cooperative learning in the teaching materials of addition and subtraction of fractions are still very low. This is proved by the average score of students' learning outcomes that is only 51.75 (below the Minimum Completeness Criteria). Because the learning activities are monotonous which means that learning does not vary when delivering the subject material. Students' enthusiasm, interest, and activity decreased due to difficulties in working and solving the worksheets. 2) With applying jigsaw-type cooperative learning, students' activities in individual learning, group learning, learning enthusiasm, attention, collaboration, communication, and discipline, overall have shown well as expected. 3) After implementing jigsaw-type cooperative learning in mathematics learning, students' learning outcomes showed improvement. This is proven from the acquisition results of the first cycle average score is 60.75 and the average score in the second cycle reaches 75, above the Minimum Completeness Criteria (KKM) of 55. Keywords: Jigsaw; Mathematics; Learning OutcomesAbstract The background of this research is from the results of initial observations which show that the children only listen, take notes, memorize, and students are not active to be able to find their own concepts, so it resulting in low learning outcomes. With that background, the researchers took the initiative to make improvements using the Jigsaw-Type Cooperative method. The result of this classroom action research, obtain that: 1) Students' learning outcomes in mathematics subjects before using jigsaw cooperative learning in the teaching materials of addition and subtraction of fractions are still very low. This is proved by the average score of students' learning outcomes that is only 51.75 (below the Minimum Completeness Criteria). Because the learning activities are monotonous which means that learning does not vary when delivering the subject material. Students' enthusiasm, interest, and activity decreased due to difficulties in working and solving the worksheets. 2) With applying jigsaw-type cooperative learning, students' activities in individual learning, group learning, learning enthusiasm, attention, collaboration, communication, and discipline, overall have shown well as expected. 3) After implementing jigsaw-type cooperative learning in mathematics learning, students' learning outcomes showed improvement. This is proven from the acquisition results of the first cycle average score is 60.75 and the average score in the second cycle reaches 75, above the Minimum Completeness Criteria (KKM) of 55. Keywords: Jigsaw; Mathematics; Learning Outcomes